Perilaku Penggunaan Kondom dan Pelicin pada LSL di Kota Surakarta - Wardhani, Putri Kusuma; Shaluhiyah, Zahroh; Demartoto, Argyo (Jurnal Promosi Kesehatan Indonesia, 2015)
ABSTRACTUser Condom and Lubricant Behavior on Men who have Sex with Men (MSM) in Surakarta Sub-Distric: One of prevention HIV/AIDS in MSM is using condom and lubricant in having sex consistenly. MSM is a high risk population whose can be time bomb to infection of HIV/AIDS. The aim of research is identifying the factors that influence to user condom and lubricant behavior on the MSM in Surakarta. The type of this research is explanatory research with cross sectional approach. The subject of research is men who have sex with men (MSM) in Surakarta, with sample of 198 people. The result of analysis bivariate variable that related to behavior of condoms user and lubricant is attitude (Ï = 0.000) and level of knowledge about condoms and lubricant (Ï = 0.001). The results of experiment regression logistic is showing the most influence variable to behavior condoms user and lubricants in Surakarta is attitude (OR = 2,502) the meaning is support respondent will lean using condom and lubricant consistently by 2,502 times than respondents less support.Keywords : Behavior, condom and lubricant, MSM